Rearing wolves to our own destruction : slavery in Richmond, Virginia, 1782-1865 - Takagi, Midori, 1962- (University Press of Virginia, 1999)
Richmond was not only the capital of Virginia and of the Confederacy, it was also one of the most industrialized cities south of the Mason-Dixon Line. Boasting ironworks, tobacco-processing plants, and flour mills, the city by 1860 drew half of its male workforce from the local slave population. "Rearing Wolves to Our Own Destruction" examines this unusual urban labor system from 1782 until the end of the Civil War
Keywords: Slavery -- Virginia -- Richmond -- History -- 18th century.; Slavery -- Virginia -- Richmond -- History -- 19th century.; Enslaved persons -- Virginia -- Richmond -- Social conditions.; African Americans -- Virginia -- Richmond -- Social conditions.; Richmond (Va.) -- History -- 18th century.; Richmond (Va.) -- History -- 19th century.; Esclaves -- Virginie -- Richmond -- Conditions sociales.; Noirs américains -- Virginie -- Richmond -- Conditions sociales.; SOCIAL SCIENCE -- Slavery.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; African Americans -- Social conditions; Slavery; Enslaved persons -- Social conditions; Virginia -- Richmond; Sklaverei; Richmond, Va.; Slavernij.; Geschichte 1782-1865.; 1700-1899; History